The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1097/mjt.0b013e31817276e9
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Induced Hyponatremia: Case Report and Literature Review

Abstract: We report a case of hyponatremia in a patient that occurred 3 days after initiation of treatment with aripiprazole. The patient was a 50-year-old man admitted to an inpatient psychiatric unit for exacerbation of schizophrenia. He was started on aripiprazole and developed hyponatremia that resolved when the medication was stopped. We postulate that the hyponatremia was due to an aripiprazole-induced syndrome of inappropriate secretion of antidiuretic hormone. There have been numerous case reports in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Four other cases of possible aripiprazole-related hyponatremia have been reported in the literature. 22,[27][28][29] In two of these cases, hyponatremia occurred within days of aripiprazole dosage titration to 20 mg per day; in two cases, the patient was reported to be receiving other psychotropic medications that have been associated with SIADH. Our patient was also prescribed bupropion hydrochloride 150 mg twice daily and a high but stable dose of sertraline (300 mg per day).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Four other cases of possible aripiprazole-related hyponatremia have been reported in the literature. 22,[27][28][29] In two of these cases, hyponatremia occurred within days of aripiprazole dosage titration to 20 mg per day; in two cases, the patient was reported to be receiving other psychotropic medications that have been associated with SIADH. Our patient was also prescribed bupropion hydrochloride 150 mg twice daily and a high but stable dose of sertraline (300 mg per day).…”
Section: Discussionmentioning
confidence: 95%
“…Serotonin-mediated effects at the 5-HT 2 and 5-HT 1 receptors on the kidney drive ADH release within the CNS. 21,22 These effects may also lead to a "resetting of the osmostat," or lowering of the sodium threshold by which ADH release is stimulated. 14 As a result, patients with this condition may have lower baseline sodium levels.…”
Section: Discussionmentioning
confidence: 98%
“…Hyponatremia is an adverse effect described both in the case of classical and atypical antipsychotics. It is postulated that the etiopathogenesis of hyponatremia in atypical antipsychotics is mediated by the action of serotonin, both by the release of ADH induced by the stimulation of central receptors 5-HT2 and 5-HT1c and by the increase in the effects of ADH at the renal medullary level [15]. In the case of typical antipsychotics, prolonged blockade of dopamine D2 receptors stimulates the release of ADH and increases its peripheral response [16].…”
Section: Hyponatremia and Antipsychoticsmentioning
confidence: 99%
“…There are currently presentations for oral, parenteral and prolonged release treatment. Literature collects cases of aripiprazole-induced hyponatremia both in patients who developed the symptoms at the start of treatment [15] and in increasing the dose [26], improving in all of them the clinical symptoms with interruption of treatment and water restriction.…”
Section: Aripiprazolementioning
confidence: 99%
“…2 However, in most published reports, the drug dosage comparison and the risk association of concomitant interaction are not provided. 2,3,9,[14][15][16][17][18][19][20][21][22][23][24] A 2010 study examining the frequency of reporting hyponatremia with SGA medications in a drug safety database concluded that hyponatremia associated with SGA medications is likely to be underreported because of the concomitant use of other medications known to cause hyponatremia (eg, thiazide diuretics) and potential interaction. 2 The purpose of this systematic review was to examine published cases reporting the use of SGAs and the occurrence of hyponatremia in patients with schizophrenia to inform physicians prescribing SGAs.…”
Section: Introductionmentioning
confidence: 99%